Investor Activism and Financial Market Structure - Noe, Thomas H. (Review of Financial Studies, 2002)
This article investigates investor activism when there are a number of strategic investors that are capable of intervening in corporate governance. These strategic investors can monitor and/or trade in anonymous financial markets. In equilibrium, a core group of monitoring investors emerges endogenously to curtail managerial opportunism. These core activists both intervene and trade aggressively. Although the smallest investors are passive, there is no monotonic relationship between the size of preexisting shareholdings and activism. In fact, among those investors who choose activism, those with the smallest holdings are the most aggressive.